A Mixed Methods Model of Learning Management Based on King Rama 9’s Royal Initiatives and Philosophy for Improving Learning and Teaching Management among Business Administration Lecturers in the Faculty of Management Science, Phranakhon Rajabhat University - Butchiwan, Phairoj; Udom, Chanthana (JOURNAL OF SOUTHERN TECHNOLOGY, 2021)
A suitable learning management model which allows to recognize the King Rama 9’s royal initiatives and philosophy as well as to efficiently develop an individual’s potential and business administrative skills needed the 21st century aims to examine the contextual and input factors, to create a model, and to ensure the consistency between the model, the empirical data, and assessing mixed methods model of learning management based on King Rama 9’s royal initiatives and philosophy for improving learning and teaching management among business administration lecturers in the Faculty of Management Science, Phranakhon Rajabhat University. A mixed methods data collection was conducted from the literature on King Rama 9’s royal initiatives and philosophy, through questionnaires, interviews, and model assessment forms whose responses were received from business administration lecturers, students, and key informants. Statistics used for data analysis comprised frequency, percentage, mean, standard deviation, range, skewness, kurtosis, correlation coefficient analysis, factor analysis, path analysis, structural equation modeling, descriptive and content analysis. The findings demonstrated that (1) contextual factors consisted of building relationship, cooperation, participation, individual experience in carrying on the King Rama 9’s royal initiatives and philosophy between the university, lecturers, and students. The university’s policies, awareness of its mission and strategy in continuing the King Rama 9’s royal initiatives and philosophy for sustainable local development, and input factors encompassed teachers, supporting factors, and learners. (2) The model involved 5 factors including understanding, accessing, developing, business administration knowledge, and skills needed in the 21st century. (3) The model was consistent with the empirical data whose Chi-square (χ2) = 183.78, df = 157, p = 0.071, (χ2) /df = 1.171, SRMR = 0.016, RMSEA = 0.019, GFI = 0.96, AGFI = 0.94, CFI = 1.00, and CN = 476. These factors could describe the skills needed in the 21st century with a variance of 88 and the overall model assessment was accurate, suitable, and had a highest possibility for application. Furthermore, this model can be used for policy setting, supporting and promoting, developing curriculum, and providing learning experience in which Phranakhon Rajabhat University, Business Administration Department, Faculty of Management Science, curriculum committee, lecturers and students are involved.